Antibody Rapid Test Results in Emergency Medical Services Personnel during COVID-19 Pandemic; a Cross Sectional Study - Saberian, Peyman; Mireskandari, Seyed Mohammad; Baratloo, Alireza; Hasani-Sharamin, Parisa; Babaniamansour, Sepideh; Aliniagerdroudbari, Ehsan; Jamshididana, Mahnaz (Archives of Academic Emergency Medicine, 2021)
Introduction: Like other infectious diseases, it is expected that COVID-19 will mostly end with the development of neutralizing antibody immunity. This study aimed to evaluate the value of COVID-19 antibody rapid test assessment in emergency medical services (EMS) personnel. Methods: This cross-sectional study was conducted in Tehran, Iran from 20th March until 20th May 2020. The results of chest computed tomography (CT) scan, and antibody rapid test were compared in EMS personnel with confirmed COVID-19, as well as symptomatic and asymptomatic ones who had exposure to a probable/confirmed COVID-19 teammate. In symptomatic or asymptomatic individuals who were only IgM-positive, chest CT scan or RT-PCR was recommended. Results: A total of 243 EMS personnel with the mean age of 36.14±8.70 (range 21 to 59) years took part in this study (87.7% were males). Most of the participants (73.3%) had history of exposure. One hundred sixty-three EMS personnel were tested using either RT-PCR test or chest CT-scan or both, and 78 (47.9%) of them had at least one positive result. Among the participants who had undergone chest CT-scan and/or RT-PCR test (n=163), 78 had positive chest CT-scan and/or RT-PCR test; of these, 18 individuals had negative results for IgM and IgG. The rate of positive IgM and IgG in participants with positive chest CT-scan was 1.6 or 1.3 times more than those with negative chest CT-scan, respectively (p < 0.05). The percentage of positive results for both IgM and IgG in participants having positive RT-PCR test was 1.7 times more than those having negative RT-PCR test (p < 0.05). Conclusion: Rapid antibody test could help in diagnosis of COVID-19 in asymptomatic or symptomatic EMS personnel who did not undergo RT-PCR test or the test was reported as negative. However, its sensitivity could be enhanced through use along with other diagnostic methods.